Phylogeny of Dengue virus type 2 isolated in the Central Highlands, Vietnam - Le, Tuan Van; Thi Tuyet Van, Nguyen; Hoang Quan, Nguyen; Tho Duoc, Pham (Revista de Biología Tropical, 2017)
Dengue fever is perhaps the most important viral re-emergent disease especially in tropical and sub-tropical countries, affecting about 50 million people around the world every year. In the Central Highlands regions of Vietnam, dengue fever still remains as a major public health issue. Although four viral serotypes have been currently identified, dengue virus type 2 (DENV-2) was involved in the most important outbreaks during 2010-2012, especially, 2010 when the fatality rate highly increased. Detection of genotype of DENV-2 provided information on origin, distribution and genotype of the virus. In this study, DEN-2 isolated from dengue patients during the 2010-2012 epidemics was amplified and sequenced with E gene. The consensus sequences were aligned with reference E gene sequences of globally available Genbank. Phylogenetic analysis was performed using Neighbor-joining and Kimura 2-parameter model to construct phylogenetic tree. A total of 15 isolates (seven from 2010; one from 2011 and seven from 2012) were obtained from human serum samples. Phylogenetic analysis revealed that Asian genotype 1 is currently circulating locally in Central Highlands region. Isolates of this genotype were closely related to viruses from Thailand, Laos, and Cambodia. It indicated that these epidemics maybe imported into the Central Highlands region from South-East Asia neighbor countries. The study results would help in planning for prevention and control of dengue virus in Vietnam. Continuous monitoring of DENV genotypes is necessary to confirm the current findings and detect possible genotype shifts within the dengue viruses in the future.